A case report of Behcet's disease in a child with trisomy 8 and literature review - Zhang, Kaixi; Wei, Chenxi; Jiang, Lijun; Zhao, Xue; Su, Qingxiao; Qi, Xingjie; Zhao, Hui; Rong, Zanhua (Frontiers in Pediatrics, 2026)
ObjectiveReport a case of Behcet's disease (BD) in a child with trisomy 8 mosaicism (T8M), providing insights for the diagnosis, treatment, and prognosis of this condition.MethodsThe clinical data of an 11-year-old girl with T8M mosaicism and BD who was admitted to our hospital in August 2022 were retrospectively analyzed, and the relevant literature was reviewed.ResultsThe main clinical manifestations of the child were recurrent oral ulcers, vulvar ulcers, fever, and joint deformities of both hands. Inflammatory markers (CRP, white blood cell, IL-6, IL-17) were significantly increased, and complement C3 and C4 were decreased. Cranial MRI showed dysplasia of the corpus callosum and ventriculomegaly. BD was diagnosed according to the international standard, and genetic testing confirmed a karyotype of 47, XX, +8[9]/46, XX [31] (chimerism ratio 22.50%). After treatment with glucocorticoids combined with immunosuppressants (including thalidomide, etc.), the ulcer and inflammatory markers were rapidly relieved. However, the ulcer recurred two and a half years after drug withdrawal.ConclusionsT8M may be detected in the autoinflammatory stage of BD, before any overt hematologic manifestations appear. Children presenting with BD-like features plus developmental anomalies or refractory autoinflammation should undergo karyotyping to establish the presence or absence of T8M, thereby informing both clinical management and genetic counseling.